Sex hormone influence on female-biased autoimmune diseases hints at puberty as an important factor in pathogenesis - Yang, Qianfan; Kennicott, Kameron; Zhu, Runqi; Kim, Jooyong; Wakefield, Hunter; Studener, Katelyn; Liang, Yun (Frontiers in Pediatrics, 2023)
The majority of autoimmune diseases affect more women than men, consistent with a role of sex hormones in regulating immune responses. Indeed, many autoimmune diseases have a post-puberty onset when sex hormones start to significantly impact physiology. In addition to established effects of sex hormones on immune cell phenotypes and cytokine profiles, recent evidence suggests a key role of sex hormones in affecting immunometabolism. In this review, the current view on how puberty impact autoimmune disease pathogenesis is presented.